Development of bottled (Mangifera Indica Linn.) chutney - Hermoso, Blesilda R.; Gatchalian, Miflora M. (1979.)
This study was undertaken to develop a standard procedure for processing bottled mango chutney, a sweet spicy relish which is said to be a usual accompaniment for curry. Basing on an available kitchen-tested procedure, several variations were done on points considered critical for finished product quality. This included variations in salt concentrations, salting time and temperatures, and Brix-Acid ratios to determine which is best among the different treatment combinations. The effect of firming agents and pasteurization on chutney quality was also evaluated. Results of the standardization process showed that from among the treatment combinations, the addition of 5% dry salt by weight of mangoes and storage at refrigerator temperature for 4 days were the best conditions for salting. This gave chips which were not only good in flavor but were also crisp in texture. It was also concluded that a 2:1 ratio of sugar to vinegar by wight was best for the liquid portion of the chutney because its high sugar content aid in the preservation while still retaining flavor acceptability. Results have also shown that the addition of firming agent improved the texture of the chutney chips and pasteurization did not alter this effect. A consumer type survey revealed that odor, flavor and texture of the chutney are critical to product acceptability. Hedonic ratings indicated that the product was likely moderately.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Chutney; Mango chutney